Charge Transport Orthogonality in All‐Polymer Blend Transistors, Diodes, and Solar Cells. Issue 6 (11th November 2013) - Fabiano, Simone; Himmelberger, Scott; Drees, Martin; Chen, Zhihua; Altamimi, Rashid M.; Salleo, Alberto; Loi, Maria Antonietta; Facchetti, Antonio
<x xml:space="preserve">Abstract</x> Polymer aggregation and phase separation of polymer–polymer blends are effectively tuned from self‐stratified to laterally phase‐separated by adjusting the relative solubility of the two polymers in the mixture. This is found to dramatically alter the charge transport characteristics from a preferential in‐plane to an out‐of‐plane direction, revealing the critical dependence of the resulting device performance on the film morphology and structure of the active layer. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>